Factors That Influence the Level of Banking Profitability in Indonesia - Erliana Aditya; Karin Resnik; Susy Muchtar (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the level of banking profitability in Indonesia using panel data analysis. Profitability is an important indicator reflecting a bank's financial health and is crucial in determining its sustainability and competitive advantage in the sector. This study examines the factors influencing the level of bank profitability in Indonesia. The sample used in this study was 40 conventional banks listed on the Indonesia Stock Exchange for five years (2019-2023). The sampling technique used was purposive sampling, and the analysis method used in this study was panel data regression. The independent variables in this study consisted of liquidity, capital adequacy, bank size, inflation, and bank income, while the dependent variable in this study was the return on assets. The results of the panel data regression in this study indicate that liquidity and bank size have a significant positive effect on the return on assets. Capital adequacy, inflation, and bank income do not affect the return on assets. The results of this study are expected to serve as a reference for conventional banks in increasing bank profitability by improving capital management efficiency, strengthening liquidity, and expanding the asset base. The results of this study are also expected to serve as a reference for investors in selecting banks with high liquidity and large size as indicators of better profit potential.